Kualitas 0Pelayanan dan Perilaku Keluhan Konsumen; Determinan dan Tipologi - Tauriana, Dian; Neri, Sem (Bina Nusantara University, 2010)
Understanding why dissatisfied consumers complain the way they do is a very important issue to be discussed from theoretical, managerial perspectives. As it is the main reason for the researcher to conduct this study. This study taken from DâLofts Apartment situated near to Bina Nusantara University. The method being used is non-parametric statistics to test the hypotheses and descriptive statistics to figure out the main reasons of complaining behavior. As the results show that price and lack of loyalty from the landlord are the main reasons consumerâs anger. Whilst the most provocative action they may take is to bad-mouth the quality given.Â